Timing of cambial phenology of rainforest trees as indicator of climate sensitivity of the Congo Basin biome - Basile Luse Belanganayi; Christophe Mbungu Phaka; Brice Yannick Djiofack; Félix Laurent; Kévin Liévens; Nestor K. Luambua; Trésor Bolaya; Nils Bourland; Wannes Hubau; Hans Beeckman; Tom De Mil (Global Ecology and Conservation, 2025)
The tropical forests of the Congo Basin biome are particularly diverse. The question arises whether the cambial activity of the multitude of tree species shows a periodic signal. Given the anticipated increases in temperature and changes in precipitation patterns, these forests may face significant threats impacting tree growth and carbon sequestration, highlighting the need for studies on cambial dynamics and their resistance adaptability to climate change. This study examines cambial phenology in two semi-deciduous rainforests in the Democratic Republic of Congo, each with a different precipitation pattern. The research focused on the temporal dynamics of cambial cell production and maturation in relation to tree morphological traits, leaf phenology, reproductive traits, and climatic variables. Biweekly microcores were taken from 30 trees across 10 species, and radius dendrometer data from 59 trees in 20 species complemented the study. Microsections were analyzed to identify cambial activity, supported by measured stem diameter variations. Results: revealed complex cambial dynamics without patterns of low cambial activity across or within species. Some species showed irregular cycles of activity, while others were continuously active, suggesting high resilience. Trees from the site with a defined dry season (Luki) were more responsive to temperature and precipitation, potentially increasing their vulnerability to climate change. In contrast, tree growth from the less seasonal site of Yangambi is strongly driven by internal dynamics, influenced by morphological and reproductive traits.